2006
DOI: 10.1111/j.1460-9568.2006.04838.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the GoLoco motif carrier regulator of G‐protein signalling 12 and 14 proteins in monkey and rat brain

Abstract: Regulator of G-protein signalling (RGS)12 and -14 proteins possess the RGS domain, Ras-binding domains and the GoLoco motif. Emerging evidence suggests that these proteins are involved in several cellular functions in addition to stimulation of GTPase activity of G-protein alpha subunits. However, our understanding of the role of the two proteins in brain function remains marginal. Here, we have studied the expression pattern of RGS12 and RGS14 proteins in brain at regional, cellular and subcellular levels. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
(69 reference statements)
1
27
2
Order By: Relevance
“…RGS12 has also been reported to be mostly expressed in trigeminal and dorsal root ganglia (DRG) neurons and muscle in the E14.5 embryonic mouse suggesting a role for mammalian RGS12 in myo-and neurogenesis (Martin-McCaffrey et al, 2005a), and also in the thalamus of adult monkey (Lopez-Aranda et al, 2006). Studies in COS-7 and HEK293 cells, have reported that endogenous or ectopically expressed RGS12 segregates into nuclear locations, thus suggesting its involvement in the regulation of transcription and cell cycle (Chatterjee and Fisher, 2000b;.…”
Section: Rgs12mentioning
confidence: 95%
See 2 more Smart Citations
“…RGS12 has also been reported to be mostly expressed in trigeminal and dorsal root ganglia (DRG) neurons and muscle in the E14.5 embryonic mouse suggesting a role for mammalian RGS12 in myo-and neurogenesis (Martin-McCaffrey et al, 2005a), and also in the thalamus of adult monkey (Lopez-Aranda et al, 2006). Studies in COS-7 and HEK293 cells, have reported that endogenous or ectopically expressed RGS12 segregates into nuclear locations, thus suggesting its involvement in the regulation of transcription and cell cycle (Chatterjee and Fisher, 2000b;.…”
Section: Rgs12mentioning
confidence: 95%
“…RGS14 is widely expressed in mammal tissues (Buckbinder et al, 1997;Evans et al, 2014;Jia et al, 2012;Lim et al, 2013;Martin-McCaffrey et al, 2005a;Oner et al, 2013;Vellano et al, 2013;Yasui et al, 2013;Zhao et al, 2013), such as brain (Lopez-Aranda et al, 2006;Snow et al, 1997), lymphoid organs (Larminie et al, 2004;Snow et al, 1997) and lung , and cells, such as lymphocytes (Larminie et al, 2004), in pyramidal and nonpyramidal cell types in brain cortex in astrocytes (Lopez-Aranda et al, 2006) and in low rate in platelets (Kim et al, 2006).…”
Section: Rgs14 (A28-rgs14)mentioning
confidence: 96%
See 1 more Smart Citation
“…Homogenates (for active PKA levels) and prepared membrane fractions (for G␣q protein levels) were treated with SDS buffer and processed for Western blot analysis similar to as described previously (Khan et al, 2000(Khan et al, , 2001Ló pez-Aranda et al, 2006). Homogenate proteins (395 g/lane) and membrane proteins (100 g/lane) were separated by 12% SDS-PAGE and transferred onto a polyvinylidene fluoride membrane (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18]43 Native RGS14 is found at high levels in brain of various species including mouse, rat, nonhuman primate, and human. 7,15,17,[43][44][45][46] In adult rodents, RGS14 is most highly expressed in brain, specifically in neurons. 7,17,43 Most recently, we have shown that RGS14 mRNA/protein expression is upregulated during postnatal mouse brain development reaching its highest levels in adulthood.…”
Section: Rgs14 Naturally Limits Learning and Synaptic Plasticity In Hmentioning
confidence: 99%